Pain Severity in Post-Caesarean Section and Its Preoperative Factors - Derajad Bayu Atmawan; Hanifa Agung Kurniawan; Reza Ishak Estiko; Trisya Allinda (JAI (Jurnal Anestesiologi Indonesia), 2023)
Background: According to World Health Organization (WHO), the global prevalence of cesarean section (C-section) reaches 21% of all deliveries and is expected to increase to 29% by 2030. This major surgery is associated with moderate to severe postoperative pain, which can affect postoperative recovery.Objective: This study aims to identify preoperative factors that affect post-cesarean pain with numeric rating scales 12 and 24 hours postoperative.Methods: A cross-sectional study was conducted at dr. Soehadi Prijonegoro Hospital, Sragen, Indonesia. The subject criteria are: (1) willing to participate in this study, (2) age more than 18 years old, (3) cooperative and communicative, and (4) not in disability condition. This research has conducted ethical approval by the Ethics Committee of dr. Soehadi Prijonegoro Hospital prior to the study.Results: We obtained 30 subjects, with no dropouts, aged 22 to 44 years, with 20% being older than 35 years pregnant women. Preoperative factors were multigravida, previous C-section, overweight to severe obesity, preeclampsia, fetal malposition, preterm premature rupture of the membranes, human immunodeficiency, malnutrition, preterm labor, hepatitis B, and anemia. Also, 83.3% of patients underwent emergency surgery. Most patients experienced moderate to severe pain 2 hours postoperation, and mild to moderate pain 24 hours postoperation.Conclusion: No significant correlation was found between preoperative factors and postoperative pain (p>0.05). Nonetheless, pain management should be tailored to each patient’s clinical condition.